Meeting EU cacao cadmium limits: A novel, real-time technology ensures 100% compliance for one of Peru’s largest farming cooperatives. - Atkinson, Rachel; Pulleman, Mirjam Margreet (2024)
New technology for real-time evaluation of cadmium levels in cacao has allowed the biggest cooperative in Piura, Peru — the region most affected by new EU Cadmium (Cd) limits in chocolate — to sell 100% of its stock of fine-flavor cacao, in full compliance with EU regulations. This has resulted in the cooperative paying a better price for cacao, directly benefiting 800 associated farmers in the north and 3,600 indirectly across Peru.